Strategi Lembaga Pendidikan dalam Meningkatkan Kualitas Sumber Daya Manusia Menghadapi Pembelajaran Abad 21 - Zahara Nora Firdausi; Bisri, Moh. (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The development of technology encourages educational institutions to improve the quality of human resources through digital learning innovations. This research aims to analyze the strategies implemented by educational institutions to enhance the quality of human resources in facing the challenges of 21st-century learning at SDIT Insan Kamil Karanganyar. The research method used is descriptive qualitative, with an observational and interview approach to describe the management strategies of human resources in the context of the development of educational technology.  Research results indicate that SDIT Insan Kamil Karanganyar has developed various innovative strategies to enhance the competencies of educators, particularly in the utilization of technology and digital media in learning. This improvement is achieved through intensive training, the application of technology in the learning process, and the development of digital-based learning methods. Educators are encouraged to be more creative, innovative, and adaptive to technological advancements in order to create a more effective and engaging learning environment for students. This research emphasizes that the integration of technology in learning is a key factor in improving the quality of human resources in Islamic educational institutions, making them competitive in the global era. The implications of this research indicate that the collaboration of managerial strategies and digital innovation is essential for educational institutions to produce superior human resources in the global era.